2022
DOI: 10.1093/bib/bbac365
|View full text |Cite
|
Sign up to set email alerts
|

A chronotherapeutics-applicable multi-target therapeutics based on AI: Example of therapeutic hypothermia

Abstract: Nowadays, the complexity of disease mechanisms and the inadequacy of single-target therapies in restoring the biological system have inevitably instigated the strategy of multi-target therapeutics with the analysis of each target individually. However, it is not suitable for dealing with the conflicts between targets or between drugs. With the release of high-precision protein structure prediction artificial intelligence, large-scale high-precision protein structure prediction and docking have become possible.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…106 The predication of protein interaction sites and folding patterns is vital for identifying optimal split sites and ensuring effective reassembly under physiological conditions. 107 Prediction algorithms that are highly customized for specific splittable protein types have also been used to produce more efficient modeling and docking structure predictions. For example, automated tools were developed for SPELL (split proteins regulated by a ligand or by light) to predict these sites with minimal spontaneous assembly.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…106 The predication of protein interaction sites and folding patterns is vital for identifying optimal split sites and ensuring effective reassembly under physiological conditions. 107 Prediction algorithms that are highly customized for specific splittable protein types have also been used to produce more efficient modeling and docking structure predictions. For example, automated tools were developed for SPELL (split proteins regulated by a ligand or by light) to predict these sites with minimal spontaneous assembly.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Combined with AlphaFold2, Bruno E. Correia et al designed a pipeline for de novo protein design, and the pipeline produced viable sequences with minimal postdesign intervention. There are many other studies on AlphaFold2-assisted protein design reported, such as references and . Within two years of AlphaFold2’s emergence, many successful applications of AlphaFold2 in biology and medicine have been reported, demonstrating its immense impact and revolutionary potential.…”
Section: Introductionmentioning
confidence: 99%